Development of thin-layer chromatographic method for determination of caffeine in black, green, and white tea - Abazi, Drita; Limani-Bektashi, Nora; Popovska, Olga (European Journal of Chemistry, 2021)
Caffeine is naturally present in tea and coffee giving the pleasant and stimulant effect. Several different types of teas, black, green, and white teas bought in market were analysis for caffeine content. The boiled sample tea was filtered through filter paper. Lead(II) acetate was used to separate tannins from caffeine followed by filtration through filter paper with a black ribbon. The liquid-liquid extraction was carried out using dichloromethane (3×5 mL) and sodium sulfate as a drying agent. The TLC method was performed on Merck precoated silica gel plates 5×10 cm (60F254, 200 μm) using either methanol or dichloromethane as solvents and the mobile phases were glacial acetic acid and ethyl acetate (95:5, v/v), while the second one was consisted of ethyl acetate and ethanol (80:20, v/v), respectfully. The Rf values were 0.36 and 0.86 for the first and the second mobile phase, respectively, in comparison to the standard caffeine. The values for pH of boiled sample teas were in the range from 4.85 to 5.80. The most abundant tea sample for caffeine was determined in green tea bought in the grocery store for health nutrition (2.04 %). The yield for tea samples from green market, white tea and two tea black samples were 0.06, 0.71, 0.07, and 0.05%, respectively. The developed TLC method can be used for determination of caffeine content in tea samples.